THE PROBLEM COMMUNAL NOISE IN CITY OF VRANJE - Bogdanović, Gordana (Journal of process management and new technologies, 2016)
Noise is any unwanted sound. This means that every sound effects (buzzing, noise, magnifier, speech and so on.), which interferes with work or rest, is noise. Communal noise generated by all noise sources that are found in the human environment, excluding the noise that occurs at the workplace in the industrial plants. It mainly comes from traffic and it’s called traffic noise. Department of Public Health Vranje is authorized and accredited professional organization that performs measurements of noise pollution in the city of Vranje. Measurement of noise in both cycles included ten measuring points that are found in a residential area. The level of acoustical load at each measurement point is followed by three measurements in the daily interval and two measurements in a night interval. Made the daytime, evening and nighttime measurements at 53 measuring points (a total of 159 measurements) over a period of 15 minutes of noise. From the 53 measuring points are higher noise level at measuring point 51 (almost all measuring points) and ranges from 2 to 47.2 dB (tab. 1 Measuring points of noise pollution Vranje-2015-day / evening / night ). The way to combat environmental noise largely depends on the degree of development, economy, culture and politics. There is no estimate on the world level about the impact of noise on the environment and human health as well as estimates of the price of that impact. The existence of a modern harmonized with European regulations normative acts will be aimed at the maximum limit and control the exposure of the population of acoustic pollution.